DE-CODE: a coding scheme for assessing debriefing interactions. (8th November 2017) - Seelandt, Julia C; Grande, Bastian; Kriech, Sarah; Kolbe, Michaela
Abstract : Debriefings are crucial for learning during simulation-based training (SBT). Although the quality of debriefings is very important for SBT, few studies have examined actual debriefing conversations. Investigating debriefing conversations is important for identifying typical debriefer–learner interaction patterns, obtaining insights into associations between debriefers' communication and learners' reflection and comparing different debriefing approaches. We aim at contributing to the science of debriefings by developing DE-CODE, a valid and reliable coding scheme for assessing debriefers' and learners' communication in debriefings. It is applicable for both direct, on-site observations and video-based coding. Methods: The coding scheme was developed both deductively and inductively from literature on team learning and debriefing and observing debriefings during SBT, respectively. Inter-rater reliability was calculated using Cohen's kappa. DE-CODE was tested for both live and video-based coding. Results: DE-CODE consists of 32 codes for debriefers' communication and 15 codes for learners' communication. For live coding, coders achieved good inter-rater reliabilities with the exception of four codes for debriefers' communication and two codes for learners' communication. For video-based coding, coders achieved substantial inter-rater reliabilities with the exception of five codes for debriefers' communication and three codes for learners' communication. Conclusion: DE-CODE is designed as micro-level measurement tool for coding debriefing conversations applicable to any debriefing of SBT in any field (except for the code medical input ). It is reliable for direct, on-site observations as well as for video-based coding. DE-CODE is intended to allow for obtaining insights into what works and what does not work during debriefings and contribute to the science of debriefing.